2011
DOI: 10.1186/1746-4269-7-19
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany, diverse food uses, claimed health benefits and implications on conservation of barley landraces in North Eastern Ethiopia highlands

Abstract: BackgroundBarley is the number one food crop in the highland parts of North Eastern Ethiopia produced by subsistence farmers grown as landraces. Information on the ethnobotany, food utilization and maintenance of barley landraces is valuable to design and plan germplasm conservation strategies as well as to improve food utilization of barley.MethodsA study, involving field visits and household interviews, was conducted in three administrative zones. Eleven districts from the three zones, five kebeles in each d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
3
40
1
Order By: Relevance
“…and it can be cropped twice a year. The main season, locally known as meher, relies on June-September rainfall, while the March-April rainfall provides moisture for a second season, known as belg (Lakew et al, 1997;Bekele et al, 2005;Shewayrga and Sopade, 2011).The greatest diversity of barley in terms of morphological types, genetic races, disease-resistant lines, and endemic morphotypes exists in Ethiopia (Orlov, 1929;Huffnagel, 1961). In Ethiopia it was cultivated by the ancient Agews as early as 3000 before Christ (Gamst, 1969) and since then the crop is grown as farmers' variety (FV's) by subsistence farmers and provide a more dependable and sustainable production for the farming community than the other cereals in the highlands of Ethiopia.…”
mentioning
confidence: 99%
“…and it can be cropped twice a year. The main season, locally known as meher, relies on June-September rainfall, while the March-April rainfall provides moisture for a second season, known as belg (Lakew et al, 1997;Bekele et al, 2005;Shewayrga and Sopade, 2011).The greatest diversity of barley in terms of morphological types, genetic races, disease-resistant lines, and endemic morphotypes exists in Ethiopia (Orlov, 1929;Huffnagel, 1961). In Ethiopia it was cultivated by the ancient Agews as early as 3000 before Christ (Gamst, 1969) and since then the crop is grown as farmers' variety (FV's) by subsistence farmers and provide a more dependable and sustainable production for the farming community than the other cereals in the highlands of Ethiopia.…”
mentioning
confidence: 99%
“…'Lhazi Ziqingke,' a purple seeded barley is preferred for preparation of Chang, a fermented drink, and the pale colored 'Garsha' is preferred for the preparation of Tsangpa, a roasted barley flour (Tashi et al, 2012). In the highland region of Ethiopia, Shewayrga and Sopade (2011) identified 15 barley landraces and 20 main barley foods and drinks associated with those varieties. These distinct landraces and colored grains are examples of selection for 'perceptual distinctiveness' which enables farmers and consumers to quickly associate specific varieties with agronomic, and end-use qualities (Gibson, 2009).…”
Section: Model 3 Farmer-based End-use Selection: Development Of Folkmentioning
confidence: 99%
“…Tsegaye and Berg (2007b) reported 14 different homemade dishes from tetraploid wheats in East Shewa, central Ethiopia while Eticha et al (2009) reported 17 different homemade dishes of barley (Hordeum vulgare) landraces in West Shewa, central Ethiopia; and Shewayrga and Sopade (2011) reported more than 20 types of homemade dishes and beverages which can be prepared from different barley landraces in North Eastern Ethiopia highlands.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse food types are the results of different landraces of different food crops which contain different end use qualities (Asfaw, 2000;Tsegaye and Berg, 2007b;Eticha et al, 2009;Geleta et al, 2009;Shewayrga and Sopade, 2011). Tsegaye and Berg (2007b) reported 14 different homemade dishes from tetraploid wheats in East Shewa, central Ethiopia while Eticha et al (2009) reported 17 different homemade dishes of barley (Hordeum vulgare) landraces in West Shewa, central Ethiopia; and Shewayrga and Sopade (2011) reported more than 20 types of homemade dishes and beverages which can be prepared from different barley landraces in North Eastern Ethiopia highlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation